Electrophysiological diagnosis and patterns of response to treatment of botulism with neuromuscular respiratory failure - Subsai Kongsaengdao (2018)
In this study we describe the electrophysiological findings in botulism patients with neuromuscular respiratory failure from major botulism outbreaks in Thailand. High-rate repetitive nerve stimulation testing (RNST) of the abductor digiti minimi (ADM) muscle of 17 botulism patients with neuromuscular respiratory failure showed mostly incremental responses, especially in response to >20-HZ stimulation. In the most severe stage of neuromuscular respiratory failure, RNST failed to elicit a compound muscle action potential (CMAP) of the ADM muscle. In the moderately severe stage, the initial CMAPs were of very low amplitude, and a 3-HZ RNST elicited incremental or decremental responses. A 10-HZ RNST elicited mainly decremental responses. In the early recovery stage, the initial CMAP amplitudes of the ADM muscle improved, with initially low amplitudes and an incremental response to 3- and 10-HZ RNSTs. Improved electrophysiological patterns of the ADM muscle correlated with improved respiratory muscle function. Incremental responses to 20-HZ RNST were most useful for diagnosis. The initial electrodiagnostic sign of recovery following treatment of neuromuscular respiratory failure was an increased CMAP amplitude and an incremental response to 10-20-HZ RNST. © 2009 Wiley Periodicals, Inc.